2018
DOI: 10.1007/s12035-018-0954-7
|View full text |Cite
|
Sign up to set email alerts
|

BIG2-ARF1-RhoA-mDia1 Signaling Regulates Dendritic Golgi Polarization in Hippocampal Neurons

Abstract: Proper dendrite development is essential for establishing neural circuitry, and Rho GTPases play key regulatory roles in this process. From mouse brain lysates, we identified Brefeldin A-inhibited guanine exchange factor 2 (BIG2) as a novel Rho GTPase regulatory protein involved in dendrite growth and maintenance. BIG2 was highly expressed during early development, and knockdown of the ARFGEF2 gene encoding BIG2 significantly reduced total dendrite length and the number of branches. Expression of the constitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 65 publications
0
17
1
Order By: Relevance
“…Recruitment of cortactin and Dyn2 to the Golgi is dependent on actin polymerization activated by Arf1, a Arf family GTPase, which regulates membrane trafficking and organelle structure [ 52 ]. Recent studies reported that the active GTP-bound form of Arf1 is functionally required for Golgi tubule formation in HeLa cells [ 53 ], and BIG2-ARF1-RhoA-mDia1 signaling controls dendritic Golgi polarization in pyramidal neurons in vitro and in vivo [ 36 ]. Furthermore, dynamin was found to be involved in the formation of Golgi outposts when activated by RhoA in the Golgi [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recruitment of cortactin and Dyn2 to the Golgi is dependent on actin polymerization activated by Arf1, a Arf family GTPase, which regulates membrane trafficking and organelle structure [ 52 ]. Recent studies reported that the active GTP-bound form of Arf1 is functionally required for Golgi tubule formation in HeLa cells [ 53 ], and BIG2-ARF1-RhoA-mDia1 signaling controls dendritic Golgi polarization in pyramidal neurons in vitro and in vivo [ 36 ]. Furthermore, dynamin was found to be involved in the formation of Golgi outposts when activated by RhoA in the Golgi [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…All animal protocols were reviewed and approved by the Institutional Animal Care and Use Committee of Chungnam National University. Primary neurons were cultured according to previously described protocols [ 36 ]. Briefly, hippocampi were dissected from rat embryos (embryonic [E] day 19), trypsinized, and triturated through a glass Pasteur pipette.…”
Section: Methodsmentioning
confidence: 99%
“…ARFGEF2 encodes BIG2, a guanine nucleotide-exchange factor involved in vesicle trafficking between endosomes and the TGN during cortical development [130]. A more recent study performed in hippocampal neurons suggests that BIG2 regulates dendritic Golgi polarization and controls dendritic growth and maintenance through ARF1 [131]. BIG2 also directly binds to ARF4, which mediates its recruitment at TGN membranes [132].…”
Section: Golgi Stress In Microcephalymentioning
confidence: 99%
“…In bipolar epithelial neural stem cells, the Golgi apparatus shows very specific and noncanonical features [40]. Reelin [41][42][43], liver kinase B1 (LKB1) [36,37], PITPNA/PITPNB [44], STK25 [36], and Brefeldin A-inhibited guanine exchange factor 2 (BIG2) [45] regulate Golgi subcellular localization. Figure 2 illustrates the related signaling pathways contributing to polarized dendrite morphogenesis in adult-born neurons.…”
Section: Roles Of the Golgi Apparatus In Neurorestoration 41 Golgi Amentioning
confidence: 99%